Aggressive Tax Planning of a State-Owned Company : A Study of State-Corporate Crime - Noora Hiltunen; Myllynen, Maileen; Savolainen, Juho; Tabit, Sofia (My University, 2025)
In January 2025, a report was published by a Finnish Non-governmental organisation Finnwatch, claiming that a Finnish majority state-owned energy company Fortum is engaging in aggressive tax planning. The report mainly included claims of cross-border profit shifting to states with more favourable tax treatment for corporations. In its public communications Fortum denied accusations of aggressive tax planning and highlighted cost-effective responsibility in its tax solutions. There is extensive regulation in place, enacted by the European Union and the Finnish state, aiming to eradicate harmful tax practices. Regardless, corporate tax avoidance in a multitude of forms prevails, as crimes committed by powerful parties, such as large multinational corporations, fail to be recognized sufficiently. This thesis recognizes a structural relation of states and corporations, which plays a significant part in enabling aggressive tax planning, which in turn is found to have harmful consequences on public finances. The aim of this thesis is to shed light on this relation and to better understand its consequences. This thesis employs a case study method to examine the underlying structures and complicity of policymakers in enabling harmful tax practices, specifically aggressive tax planning. Theories relevant to corporate crime criminology, including state-corporate crime and regimes of permission, are adopted as tools for this examination. It is concluded that even though aggressive tax planning does not overstep the line of illegality and remains distinct from both civil law-defined tax avoidance and criminalized tax evasion, the harm to public economies is significant. The consequences caused to public economies by aggressive tax planning and criminalized tax evasion are even found to be identical at times. However, due to loopholes and technicalities, actions may not fall under tax evasion, therefore avoiding the label of criminality. This thesis calls for a rethinking of the relationship between states and corporations, as well as corporate structures as a measure to mitigate these effects.

Tammikuussa 2025 kansalaisjärjestö Finnwatch julkaisi raportin, jossa valtion enemmistöomisteisen yhtiön Fortumin väitettiin harjoittavan aggressiivista verosuunnittelua. Kyseinen raportti sisälsi pääasiassa syytöksiä voitonsiirroista edullisemman verokohtelun maihin. Fortum vastasi syytöksiin peräänkuuluttaen omien veroratkaisujensa kustannustehokkuutta sekä vastuullisuutta ulkoisessa viestinnässään. Haitallisten veroratkaisujen kitkemiseksi laadittua verolainsäädäntöä on kattavasti voimassa sekä EU-tasolla että Suomessa. Siitäkin huolimatta veronkierto on yhä yleistä sen monissa muodoissaan, sillä tällaisia valta-asemassa oleville osapuolille tyypillisiä rikoksia ei usein tunnisteta riittävästi. Tässä tutkielmassa nostetaan esiin valtioiden ja suurten yhtiöiden välisiä rakenteellisia riippuvuuksia. Nämä suhteet ovat merkittävässä roolissa mahdollistamassa aggressiivista verosuunnittelua, joka aiheuttaa negatiivisia seurauksia julkiselle taloudelle. Tämän tutkielman tavoitteena on korostaa näitä suhteita ja tunnistaa niiden seurauksia. Kyseessä on tapaustutkielma, joka tutkii syviä rakenteellisia seikkoja sekä päättävien tahojen osallisuutta, mitkä osaltaan mahdollistavat haitalliset verokäytännöt, kuten aggressiivisen verosuunnittelun. Kriminologiset teoriat, kuten epälegitiimi toiminta johon valtiot ja yhtiöt syyllistyvät yhdessä eli “state-corporate crime” sekä rikollisuutta mahdollistavat järjestelmät eli “regimes of permission”, ovat keskeisiä työkaluja tapauksen tutkimisessa. Tutkielmassa otetaan huomioon, että aggressiivinen verosuunnittelu on lain sanamuodon mukaista toimintaa, eikä se siten ylitä laittomuuden rajaa tai täytä rikoksen tunnusmerkkejä. Aggressiivisen verosuunnittelun aiheuttamat negatiiviset vaikutukset julkiseen talouteen voivat kuitenkin vastata, ja joissain tapauksissa jopa ylittää, kriminalisoitujen veropetosten seuraukset. On kuitenkin tyypillistä, että porsaanreikien ja muotoseikkojen vuoksi haitallisia verokäytäntöjä ei voida luokitella rikoksiksi, kuten veropetokseksi. Tutkielmassa korostetaan tarvetta valtioiden ja yhtiöiden välisten suhteiden sekä yhtiörakenteiden uudelleenarvioinnille, jotta negatiivisia vaikutuksia voitaisiin lieventää.
Keywords: Aggressive tax planning, tax avoidance, tax competition, state-corporate crime, multinational corporations, state-owned enterprises, EU taxation